Social studies preservice teachers' experience of technology integration (Qualitative research in UPI Campus Sumedang) - Hanifah, N; Isrokatun, I; Aeni, A N (Journal of physics. Conference series, 2019)
This research examined preservice teacher's experiences of technology integration in social studies as a subjects in curriculum. We recognize school-based technology integration and implementation processes are influenced by a complex ecology of people. There are abundant ways social studies students can make social studies enjoyable and meaningful to students. As an interdisciplinary subject, social studies draws upon multiple curricular contents related to the social sciences. With increased innovation and technological developments, access becomes a concern. Campuses expecting technological fluency and seamless integration into the classroom must also admit that there are students with limited skills and exposure. This study will explore which students as preservice teachers are using technology and how technology is shaping their college experiences, also able to use technology creatively to facilitate their work, expand their instructional strategies, and improve social studies teaching. This study suggests that technology indeed offered social studies student a unique opportunity to enhance social studies instruction. Further, they can have incorporated technology into the social studies curricula in many and varied ways. Use of technology made it possible for them to conduct learning activities that both increased students' interest in social studies and improved their problem solving ability and higher order thinking skills.